Social character development of Madura children left to migrate in Bangkes Village - Rahman, Baitur; Mustofa, Moh. Solehatul; Priyanto, Agustinus Sugeng (Journal of Educational Social Studies, 2024)
The phenomenon of migrant families is one form of parenting that causes limitations for parents in carrying out their roles and functions as caregivers and educators of children. Children's interaction with parents is limited, causing a lack of control over children's character development. The purpose of this study is to examine in depth the role of the family in instilling children's social character and to analyse the role of kiai in shaping the social character of children left behind by migrants in Bangkes Village. This research method is qualitative by involving caregivers, namely mothers and aunts and Kiai figures as the main informants. This research was conducted on Madurese migrants' family in Bangkes Village, Kadur Sub-district, Pamekasan Regency with data collection methods of observation, interview, and documentation. The results showed that the parenting role of children in Bangkes village was carried out by mothers and family, namely aunts. The form of family parenting is effective in shaping the social character of children who are more independent, responsible and have integrity based on their level of education and knowledge. In addition, the role of Kiai as a religious figure helps shape and provide control over children's character through understanding moral and religious values. The implications of this research provide recommendations for collaborative parenting plans between families and religious leaders.